Fases de uma audiência preliminar no Juizado Especial Criminal: Uma abordagem linguístico-interacional - Machado, Ana Carla; Vieira, Amitza Torres (Language and Law / Linguagem e Direito, 2023)
This paper aims to investigate the overall structural organization of a preliminary hearing in the Special Criminal Court, a court which is responsible for judging misdemeanor cases. The research is based on the theoreticalmethodological approach of Conversation Analysis (Sacks et al. 2003 1974), focusing on studies of institutional talk-in-interaction (Drew e Heritage 1992; Roberts e Sarangi 2005; Robinson 2013), as well as combining concepts from Interactional Sociolinguistics (Gumperz 1999; Gumperz, J.J. 2002). The results show four phases: opening, that occurs when the conciliator takes a roll call and greets the parties; presentation of the problem, which happens when they explain legal concepts to laypeople; offering to file the case, when the conciliator tries to persuade the parties to file and close the case; and ending, that takes place when the parties sign the paper agreement.